Persistent use of nitrous oxide for anaesthesia in European hospitals despite its harmfulness to the climate – how emission taxation can achieve the coupling of cost-effectiveness and climate protection: observational study - Ferdinand Lehmann; Christian M Schulz; Dominik Leicht; Scott Brady; Anna Fuhrmann; Jens Prütting; Max Georg Hügel; Daniel Hörr; Michael Sander (BMC Health Services Research, 2023)
Abstract Background Health care has the intrinsic obligation to preserve health. This concept is also applicable to planetary health. Nitrous oxide (N2O) lacks clinical indications in modern anaesthesia, while it is a high-potential greenhouse gas. Its seemingly low cost contrasts with the consequential externalised socio-economic costs due to its contribution to the climate crisis, which is approximately €698 per emitted ton of CO2 equivalent. This difference can be internalised through emission taxation. In this study, we aim to evaluate how much N2O – total amount and converted to CO2 equivalent – is used at a German university hospital and compare this amount to that used at European hospitals. Furthermore, how the cost of N2O usage changes under different emission taxation scenarios is calculated. Methods This trial was a retrospective observational study at a German university hospital with approximately 1,250 beds between 2016 and 2020. Additionally, five European hospitals from the Health Care Without Harm Network were used for comparison from a European perspective. The main outcome parameters were the amount of N2O used, in total and converted to CO2 equivalent, and the total cost at emission taxation of €0, €25, €55 and €698 per ton CO2 equivalent. Results At the peak, 2,104 tCO2 equivalent in N2O was emitted in 2019. The actual cost was €14,040 in this year, while the corresponding socio-economic damage due to the climate crisis was almost €1.5 million. Other European hospitals showed comparable amounts of emissions. Conclusions The annual peak amount of emitted N2O corresponded to the total annual greenhouse gas emission of 188 people in Germany. To achieve a drastic reduction in use, the abandonment of recommendations by anaesthesiologic societies appears necessary, in addition to an internalisation of future costs via emission taxation, which will cause inadequate cost for a medication without relevant benefit or indication. To that end, the inclusion of health sector emissions within national or international greenhouse gas taxation, for example, the European Union Emissions Trading System, appears necessary and expedient in view of the urgent need to address the ecological transformation. Trial registration The trial was registered with the German Clinical Trials Register, identifier DRKS00024973 on 12/04/2021.